The Effect Of The Problem Based Learning Model On Students' Reasoning Abilities In Solving Story Problems On The SPLDV Material For Grade VIII - Yohannes F Siahaan; Ropinus Sidabutar; Yanty Maria Marbun (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The purpose of this study was to determine the effect of the Problem-Based Learning Model on students' reasoning ability in solving story problems in class VIII at the UPTD of SMP N 2 Pematang Siantar. The study used a pre-experimental design with classes VIII-8 as subjects, and the author employed a quantitative approach. The design used by the researcher was a One-Shot Case Study. Based on the results of data analysis and discussion, it can be concluded that the use of the Problem-Based Learning Model has a positive and significant effect on students' reasoning ability in solving story problems in class VIII at the UPTD of SMP N 2 Pematang Siantar in the 2025/2026 academic year. A positive influence is shown through the regression equation where Y = 40.826 + 1.168 where the b value = 1.168. This influence is shown through the T-Test with Tcount > Ttable (3.926 > 1.701) or (sig.) < 0.05 (0.000 < 0.05) then Ho is rejected and Ha is accepted which means there is a positive and significant influence of the Problem Based Learning Model on Students' Reasoning Ability in solving story problems on the SPLDV material. The contribution of variable X (Problem Based Learning Model) to variable Y (Student Reasoning Ability) is 67.4%.